Impact of die carrier on reliability of power LEDs - Kyatam, Shusmitha (2021)
High power light emitting diodes (LEDs) suffer from heating effects that have a detrimental impact on the devices characteristics. The use of LED carriers with high thermal conductivity promotes extraction of heat away from the LED junction. Different materials can be used for this purpose, such as alumina, aluminium nitride, and silicon. Diamond has also been gaining momentum for demanding heat management applications. In order to evaluate the impact of the carrier material on the reliability of the devices, the junction temperature of Cree white XLamp XB-D LEDs was obtained with Ansys for various carriers and different LED current levels. The impact of the junction temperature on the LED’s lifetime, emission intensity, footprint, and wavelength stability was then evaluated for each carrier based on the datasheet of the devices. The results provide additional knowledge regarding the impact of the carrier on the performance of the LED.